2021
DOI: 10.1111/1462-2920.15534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying glyphosate resistance in bacteria

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 178 publications
0
29
0
1
Order By: Relevance
“…As with other toxic compounds, bacteria may develop resistance by reducing membrane permeability, metabolism, or efflux. For glyphosate, resistance has been described as a result of efflux via a membrane transporter and metabolism mediated by an enzyme with a single base pair mutation in the gene aroA, that is typically responsible for the synthesis of aromatic amino acids [158]. Of concern is that laboratory experiments have demonstrated that the exposure of Salmonella enterica Typhimurium and E. coli to several commonly used herbicides (dicamba, 2,4,-dichlorophenoxyacetic acid, and glyphosate) changes the antimicrobial susceptibility of these organisms [159].…”
Section: Herbicidesmentioning
confidence: 99%
“…As with other toxic compounds, bacteria may develop resistance by reducing membrane permeability, metabolism, or efflux. For glyphosate, resistance has been described as a result of efflux via a membrane transporter and metabolism mediated by an enzyme with a single base pair mutation in the gene aroA, that is typically responsible for the synthesis of aromatic amino acids [158]. Of concern is that laboratory experiments have demonstrated that the exposure of Salmonella enterica Typhimurium and E. coli to several commonly used herbicides (dicamba, 2,4,-dichlorophenoxyacetic acid, and glyphosate) changes the antimicrobial susceptibility of these organisms [159].…”
Section: Herbicidesmentioning
confidence: 99%
“…Microorganisms present in aquatic environments may suffer selective pressure due to contact with herbicides ( Iori et al., 2020 ). Bacteria can be selected for specific resistance to glyphosate through the elevation of the production of the EPSPS; herbicide degradation; detoxification by covalent modification; and decreasing uptake and increasing export of herbicide ( Hertel et al., 2021 ). Nevertheless, we found no reports in the literature about response systems that were not induced by the selective pressure of specific xenobiotics.…”
Section: Resultsmentioning
confidence: 99%
“…However, different molecular mechanisms underlying glyphosate resistance in bacteria were also highlighted demonstrating the adaptation capacity of some species thanks to genomic alterations, although A. kunkeei does not appear in such list. The mechanisms included an increased production of EPSPS, the degradation or detoxification of the herbicide, and the uptake decrease combined with an export increase of such agrochemical (Hertel et al ., 2021). Reldan, an organophosphorus insecticide, having a broad range of actions is used to eradicate pests from agricultural and farming regions (Nita‐Lazar et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%